Eulithis mellinata (Fabricius, 1787), nova vrsta v slovenski favni metuljev (Lepidoptera: Geometridae) - Lesar, Tone (Acta entomologica slovenica (Ljubljana), 1998)
As a result od several nights hunts with a UV-trap near Maribor, north-eastern Slovenia, a month species new to the Slovenian moth fauna was registred. It has also been found at Lendava, near the Hungarian border
Keywords: entomologija; metulji; zoologija; zoology